Pengaruh Jenis dan Konsentrasi Larutan Perendam Alami Terhadap Perkecambahan Biji dan Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq). - A Amirudin; Endah Dwi Hastuti; Erma Prihastanti (Jurnal Akademika Biologi, 2015)
Oil palm (Elaeis guineensis Jacq) is one of the leading commodity Indonesian plantation product that has economic value International market. In the process of oil palm cultivation experience problems due to oil palm seeds have a hard endocarp and contain lignin content is high enough that it is difficult to germination. Purpose of this study the effect of the type and marinade solution concentration as well as the interaction between the type and concentration of  the  solution  marinade  for  seed  germination  and  seedling  growth  of  oil  palm  (Elaeis guineensis Jacq). This research is random full factorial design consisting of two factor 2 x 5. The first factor is the type of marinade: coconut water and cow urine, the second factor is the concentration of  the solution marinade. This study uses 10 treatments with 3 repetitions. Parameters observed that the percentage of germination, plant height, leaf number, leaf color, number of roots, fresh weight and dry  weight.  Analysis of the data used is Analysist of Variances (ANOVA) showed a significant effect if it continued with Duncan’ Multiple Range Test (DMRT) at the level of 95%. The results showed that the type of marinade effect on plantheight. The results showed that the percentage of seed germination is influenced by the concentration of soaking solution with the highest rates at a concentration of 75% was kind of marinade between coconut water and cow urine had no effect. Oil palm seedling growth is influenced by the type of solution shredded  coconut milk and cow urine concentration and interact with the marinade. Type shredded cow urine at a concentration of 75% to produce the highest seedling growth.Keywords: Oil Palm (Elaeis guineensis Jacq), Coconut milk, Cow urine,     Germination, Seed